Rock art, ancestors and water: the semiotic construction of landscapes in the central Andes (2017)
This thesis focuses on a large complement of rock art on the Fortaleza Ignimbrite (FI), a distinct geological formation, at the headwaters of the Fortaleza and Santa rivers (Ancash, Peru). The pairing of the stratigraphy of carved and painted rock art with the archaeological stratigraphy and radiocarbon results in three puna rock shelters, in both watersheds, and one tomb, down valley in the quechua ecozone, is employed to answer the question of when these works were produced and to develop a typological sequence, and a spatio-temporal map of the styles and traditions for the rock art of the FI, spanning 3,000 years. As landscape art, central Andean rock art offers clues regarding relationships between ancestor veneration and the negotiation of rights to water through time, and as the rock art of the FI sits at the nexus of political, economic and religious realms, and is located at strategic places of power...